Implementasi Sikap Religius Pada Mata Kuliah Alislam dan Kemuhammadiyahan di Program Studi Magister Manajemen Universitas Muhammadiyah Tangerang - Adima, Eko Fauzan; Silvia, Novita; Maulana, Mulan; Rizki, Riki (Penerbit Minhaj Pustaka, 2024)
This research certainly has several objectives, including the following: (1) To explain the implementation of Al-Islam and Muhammadiyah Education (AIK) in the Master of Management Study Program, Muhammadiyah University, Tangerang. (2) To describe the role of Al-Islam and Muhammadiyah education in the religious attitudes of students at the Master of Management Study Program, Muhammadiyah University, Tangerang. This research is research using analytical descriptive methods with a qualitative approach. The researcher applied observation, interview and documentation techniques. Observations and interviews will produce primary data sources, will provide researchers with information about the Al-Islam and Muhammadiyah education process, and its role in improving students' religious attitudes. The factor that supports the success of the role of Al-Islam and Muhammadiyah education and improving students' religious attitudes is the existence of an education system that is uswah hasanah, so that interaction between students and lecturers can be achieved. Apart from that, secondly, physical facilities in the form of mosques and libraries which are representative facilities for worship and study. The third is an Information Technology system that can increase student information. The fourth is lecturer staff who meet the qualifications because they are activists with a teaching or teaching professional background, supported by comfortable environmental conditions, without any mental and moral tension among students. The obstacles are heterogeneity and habits of daily religious life.